Comparative Analysis of Corner Joint Designs for Modular Housing Structures - Mohd Zamzuri, Muhamad Syafiq Aiman; Mohammad Sukri Mustapha; Mohd Rasidi Ibrahim (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study examines the structural performance of three modular house joint designs using SolidWorks for CAD modelling and ANSYS for static analysis. Emphasizing modular housing's benefits in emergency scenarios, the joints were evaluated for equivalent stress, shear stress, deformation, and safety factors using A36 carbon steel, stainless steel, and aluminium alloy. Results indicate Joint 2 as the optimal choice for roof and base connections, with A36 carbon steel emerging as the best material overall. These findings highlight the importance of joint design and material selection in enhancing the resilience and adaptability of modular structures.